Helping Teachers Manage Students' Externalizing Behaviors by Identifying Behavioral Cusps - Alexis Boudreault; Julie Lessard (Canadian Society for Studies in Education, 2020)
Abstract: Managing students' externalizing behavior is an essential but difficult and stressful task for many teachers. As a result, some teachers use ineffective intervention strategies, which end up exacerbating externalizing behavior. This paper considers the theoretical model of behavioral cusps as an avenue to support teachers in the management of students' externalizing behavior. This model helps identify what behavioral modifications to prioritize, guiding teachers' interventions and maximizing the cost-benefits of the strategies used. Finally, this paper will discuss the educational implications of deploying this theoretical model of intervention in brief in-service teacher training, while considering the resources that are generally available in pedagogical environments.